Civil society briefs Solomon Islands. - Wignaraja, Ganeshan (Metro Manila, Philippines Asian Development Bank, 2017)
After chiefly organizations, many of the earliest civil society organizations (CSOs) in the Pacific were established by missionaries, who, in addition to their religious roles, formed youth and women groups. Today, civil society in Solomon Islands encompasses many types of groups. There is a range of both membership and nonmembership organizations, including those that are established for public benefit, and those that are established to support their members.
Keywords: Public administration -- Developing countries; Sanitation; Electronic books